Accounting Reservation of Financial Statements And its Effect on the Cost of Capital in Commercial Banks Listed on the Amman Financial Market - Al-Naimi , Fatin (The Arab Journal of Administration, 2021)
The study examined the importance of accounting reservation, and its effect on the Cost of Capital in Jordanian banks, During the period (2013-2018), empowering the entire study community, represented by (13), The researcher also used the multiple regression, to predict the existence of an accounting reservation effect on the cost of capital, and found a statistically significant impact on both cost of Equity and cost of debt, it recommended the necessity of keeping the accounting reservation in the conceptual framework of financial reporting standards and urging banks and public contributing companies to apply the accounting reservation when preparing financial statements, for its great role in reducing the cost of capital and achieving economic benefits for it. The researcher called for conducting studies and researcher on the accounting reservation, and its relationship to the asymmetry of information and the transparency of financial statements and the efficiency of financial markets, to assist professional organizations in taking appropriate decisions about keeping it within the conceptual framework for the preparation of financial reports.